Effect of Boron, Zinc and Iron on Economics of Kharif Onion (Allium cepa L.) - Pankaj Kumar Maurya; Ghanshyam Thakur; Achyut Suman; Ramesh Kumar Gupta (International Journal of Economic Plants, 2025)
The experiment was carried out during July–September, 2016 at Tirhut College of Agriculture, Dholi kothi farm, Dholi (Muzaffarpur), a campus of Dr. Rajendra Prasad Central Agricultural University, Pusa (Samastipur), Bihar (848 125), India to study the effect of micronutrient application on economics of onion (Allium cepa L.). Onion is one of the most important bulb crops globally and a major commercial crop cultivated across the country, valued both as a spice and a vegetable. Micronutrients play a vital role in fertilization programs aimed at achieving higher and more sustainable bulb yields. Therefore, the present experiment was conducted to study the effect of zinc, iron, and boron on the economics of onion. The experiment was laid out in RBD with ten treatments with three replications. The treatments includes T1 (NPKS), T2 (NPKS+soil application of ZnSO4 @ 25 ha-1), T3 (NPKS+soil application of ZnSO4 @ 50 kg ha-1), T4 (NPKS+foliar application of ZnSO4 @ 0.5% at 30 and 45 DAT), T5 (NPKS+soil application of Borax @ 10 kg ha-1), T6 (NPKS+soil application of Borax @ 15 kg ha-1), T7 (NPKS+foliar application of Borax @ 0.25% at 30 and 45 DAT), T8 (NPKS+soil application of FeSO4 @ 25 kg ha-1), T9 (NPKS+soil application of FeSO4 @ 50 kg ha-1), T10 (NPKS+foliar application of FeSO4 @ 1% at 30 and 45 DAT) replicated thrice in a RBD. The highest gross return (`Rs. 3,93,776 ha-1) and net income (`Rs. 3,06,524.05 ha-1) was calculated in treatment T3 (NPKS+soil application of ZnSO4 @ 50 kg ha-1) and B:C ratio (3.53) was calculated in treatment T2 (NPKS+soil application of ZnSO4 @ 25 kg ha-1).